2007
DOI: 10.1002/jbm.a.31545
|View full text |Cite
|
Sign up to set email alerts
|

In situ SAXRD study of sol–gel induced well‐ordered mesoporous bioglasses for drug delivery

Abstract: In this work, two systems of mesoporous bioglasses (MBGs) were sol-gel derived using block copolymer pluronic F127 and P123, respectively, as templates. A two-dimensional hexagonal (P6mm) mesoporous structure was obtained for the two systems, with d-spacing in (100) reflection of 8.49 nm for P123-templated MBG (P123-MBG) and 10.26 nm for F127-templated MBG (F127-MBG). The phase transformation behavior for the systems was elucidated using an in situ synchrotron small angle X-ray diffraction approach, with the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 35 publications
0
11
0
1
Order By: Relevance
“…Zhao et al [92] used different surfactants (P123 and F127) to prepare MBG and found that P123-MBG had higher pore volume and surface area than F127-MBG. The higher pore volume and surface area of P123-MBG led to significantly higher drug (metoclopramide)-loading efficiency (47.3%), compared with that for F127-MBG (16.6%) [92]. Arcos et al [28] prepared MBG by using three surfactants (CTAB, P123 and F127) and compared their drug (triclosan)-delivery ability.…”
Section: The Effect Of Preparation Method Composition and Mesoporousmentioning
confidence: 99%
“…Zhao et al [92] used different surfactants (P123 and F127) to prepare MBG and found that P123-MBG had higher pore volume and surface area than F127-MBG. The higher pore volume and surface area of P123-MBG led to significantly higher drug (metoclopramide)-loading efficiency (47.3%), compared with that for F127-MBG (16.6%) [92]. Arcos et al [28] prepared MBG by using three surfactants (CTAB, P123 and F127) and compared their drug (triclosan)-delivery ability.…”
Section: The Effect Of Preparation Method Composition and Mesoporousmentioning
confidence: 99%
“…The above analysis also agrees with the frontal XRD and AFM results. These hierarchical mesoporous structures have potential applications as hosts in bonding or storing more drug molecules in the drug-release system [25,26]. The protein composition and structure in the different samples synthesized under the same conditions were analyzed by a Waters HPLC and the microscopic Raman spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…The potential mechanism of MBG with a slow drug release rate is due to the existence of a large number of Si-OH groups in MBG, which play an important role in interacting with gentamicin [29]. The surfactant plays an important role in influencing the loading and release of drug from MBG powders; P123-MBG has significantly higher loading efficiency for drug (47.3%) than F127-MBG (16.6), which is attributed to the higher pore volume and surface area for P123-MBG [36]. In another study, a photo responsive coumarin derivative was grafted onto MBG particles to develop photo controlled molecular gates.…”
Section: Mbg For Efficient Drug Deliverymentioning
confidence: 97%